PENGARUH BUDAYA ORGANISASI, KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS KOPERASI, UKM, PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN PADANG LAWAS - Fahri Ismail Simamora; Nova Zulfani Panggabean; Putri Utami; Hendy Bhuana Putra; Nazla Nazla (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
This formula research internal issue is how influence culture organization on employees performance. How influence of communication on employees performance. How influence ofmotivationon employees performance. How influence ofculture organization, communicationand motivation onemployees performance. This research target is to for know influence andanalyze ofculture organization on employees performance. For know influence and analyzeofcommunication onemployees performance. For know influence and analyzemotivationonemployees performance. For know influence and analyzeculture organization, communicationand motivation onemployees performance Sample in this research amount to 36 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. Thisresearch result explain ofculture organization effect positive and significant onemployeesperformance. Communicationeffect positive and significant onemployeesperformance.Motivation effect positive and significant on employees performance.Cultureorganization,communication and motivation effect and positive and significant onemployees performanceThis formula research internal issue is how influence culture organization on employees performance. How influence of communication on employees performance. How influence ofmotivationon employees performance. How influence ofculture organization, communicationand motivation onemployees performance. This research target is to for know influence andanalyze ofculture organization on employees performance. For know influence and analyzeofcommunication onemployees performance. For know influence and analyzemotivationonemployees performance. For know influence and analyzeculture organization, communicationand motivation onemployees performance Sample in this research amount to 36 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. Thisresearch result explain ofculture organization effect positive and significant onemployeesperformance. Communicationeffect positive and significant onemployeesperformance.Motivation effect positive and significant on employees performance.Cultureorganization,communication and motivation effect and positive and significant onemployees performance